1997
DOI: 10.1172/jci119350
|View full text |Cite
|
Sign up to set email alerts
|

1,25 dihydroxyvitamin D3 stimulates phospholipase C-gamma in rat colonocytes: role of c-Src in PLC-gamma activation.

Abstract: Our laboratory has previously demonstrated that 1,25-dihydroxyvitamin D 3 (1,25[OH] 2 D 3 ) rapidly stimulated polyphosphoinositide (PI) hydrolysis, raised intracellular Ca 2 ϩ , and activated two Ca 2 ϩ -dependent protein kinase C (PKC) isoforms, PKC-␣ and -␤ II in the rat large intestine. We also showed that the direct addition of 1,25(OH) 2 D 3 to isolated colonic membranes failed to stimulate PI hydrolysis, but required secosteroid treatment of intact colonocytes, suggesting the involvement of a soluble fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 41 publications
(55 reference statements)
2
46
0
Order By: Relevance
“…This possibility appears plausible because both PLC␥1 and the AT 1 receptor have been shown previously to be excellent substrates for Src kinases in vitro (13,16). Furthermore, PLC␥1 has been shown to form a complex with c-Src in several other cell types (7,17,18). An alternative explanation for the inhibitory effect of PP1 is that Src kinase activity may be required for a phosphorylation event that is upstream from either PLC␥1 or AT 1 receptor phosphorylation in a tyrosine phosphorylation cascade.…”
Section: Resultsmentioning
confidence: 90%
“…This possibility appears plausible because both PLC␥1 and the AT 1 receptor have been shown previously to be excellent substrates for Src kinases in vitro (13,16). Furthermore, PLC␥1 has been shown to form a complex with c-Src in several other cell types (7,17,18). An alternative explanation for the inhibitory effect of PP1 is that Src kinase activity may be required for a phosphorylation event that is upstream from either PLC␥1 or AT 1 receptor phosphorylation in a tyrosine phosphorylation cascade.…”
Section: Resultsmentioning
confidence: 90%
“…Since our results show that in our cells PLC-g-1 is insensitive to EGF treatment, other mechanisms must be responsible for the permanent activation found in E5 cells. In this context it should be mentioned that in several cell systems, src-kinase can also be involved in the activation of PLC-g-1 activity (Khare et al, 1997;Reynolds et al, 1993;Singer et al, 1997). At this stage, however, whether this enhanced activation is the result of increased phosphorylation in an E5-dependent manner or an impaired PLC-g-1-speci®c phosphatase remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest a role for EGFR, but not PDGFR in mediating PLC-␥1 phosphorylation by oxidative stress. Previous studies have shown that Src family tyrosine kinases are involved in signaling events stimulated by reactive oxygen species (22)(23)(24) and Src kinase family members have also been demonstrated to phosphorylate PLC-␥1 and PLC-␥2 in vitro (25,26). To address the role of Src family kinases in H 2 O 2 -mediated phosphorylation of PLC-␥1, we utilized the selective Src family tyrosine kinase inhibitor PP2.…”
Section: H 2 O 2 Stimulates Tyrosine Phosphorylation Of Plc-␥1-mentioning
confidence: 99%